Brain Drain and Economic Development in Nigeria: Causal and Cointegration Analyses (Journal of Management and Social Sciences, 2026)
This study examined the dynamic relationships between brain drain and economic development in Nigeria from 1990 to 2024, using the Autoregressive Distributed Lag (ARDL) model with the Granger causality framework, the study first tested the direction of influence among skilled emigration, financial inflows, human capital formation, and Nigeria’s development trajectory. The causality results guided the choice of dependent and independent variables, after which the ARDL model captured both short-run adjustments and long-run equilibrium dynamics, offering clear insights into how these factors shape Nigeria’s development path. Granger causality tests were first conducted to establish the direction of influence among the variables, which guided the specification of economic development as the dependent variable. The ARDL bounds test then confirmed long-run cointegration among the series. Findings showed that literacy rate exerted a consistently positive and significant effect on economic development in both the short and long run, underscoring the central role of human capital. Brain drain had a significantly negative long-run impact on economic development, indicating structural harm to the economic development, although the short-run effects were mixed. Remittances exhibited weak and delayed short-run impacts. In the long run, they were statistically insignificant, indicating limited developmental value without structured investment frameworks. The study calls for policy actions that encourage the retention and development of skilled labour, direct remittances into productive sectors, and enhance educational quality and access. Strengthening macroeconomic fundamentals is also essential to support sustained growth. These interventions are key to reducing the adverse effects of brain drain and maximising the developmental benefits of financial and human capital inflows.Keywords:Brain drain, remittances, economic development, human capital, ARDL model